Influence of monsoon on the distribution of organic carbon in inner continental shelf core sediments, South China Sea, Malaysia - Pang, Swee Yun; Juriffah Ariffin,; Hii, Yii Siang; Norhayati Mohd Tahir, (Universiti Kebangsaan Malaysia, 2015)
Three short sediment cores (12-32 cm) from South China Sea off Southern Terengganu were collected during May (post-Northeast monsoon) and September (pre-Northeast monsoon) 2007. The concentration of total organic carbon (TOC) obtained ranged from 0.41-2.23 and 0.38-2.31% during post and pre-monsoon, respectively. TOC concentration was found to decrease with depth and distance from the coast and river mouth. In particular, station with close proximity to the coast exhibits most pronounced variation of TOC with depth. Besides spatial variation, it is noted that the seasonal variations also considerably affect the distribution and concentrations of TOC, where both near and offshore sampling stations showed significant variations in TOC content during May and September sampling. These findings suggest the importance of terrestrial organic carbon flux, physical mixing and seasonal variations in regulating the concentration and distribution of the organic carbon in the study area.